Establishment of a reverse transcription recombinase-aided amplification detection method for porcine group a rotavirus - Wang, Yushun; Nie, Mincai; Deng, Huidan; Lai, Siyuan; Zhou, Yuancheng; Sun, Xiangan; Zhu, Ling; Xu, Zhiwen (Frontiers in Veterinary Science, 2022)
Porcine rotavirus type A (PoRVA) is the main cause of dehydration and diarrhea in piglets, which has a great impact on the development of the pig industry worldwide. A rapid, accurate and sensitive detection method is conducive to the monitoring, control, and removal of PoRVA. In this study, a PoRVA real-time fluorescent reverse transcription recombinase-aided amplification (RT-RAA) assay was developed. Based on the PoRVA VP6 gene, specific primers and probes were designed and synthesized. The sensitivity of RT-RAA and TaqMan probe-based RT-qPCR was 7 copies per reaction and 5 copies per reaction, respectively. The sensitivity of the RT-RAA method was close to TaqMan probe-based RT-qPCR. The detection results of RT-RAA and TaqMan probe-based quantitative real-time RT-PCR methods were completely consistent in 241 clinical samples. Therefore, we successfully established a rapid and specific RT-RAA diagnostic method for PoRVA.